(untitled) - Lilley, James H. (Thailand, 1992)
This pamphlet provides a general review of the information available at the present time. It reports on the backgroud to EUS, its impact and the various studies into the aetiological and environmental aspects that affects its epidemiology.
Keywords: Động vật thủy sản,Aquatic animals; Bệnh,Quản trị,Diseases,Management; Châu Á,Asia